OPTIMALISASI PERAN PEMUDA SEBAGAI GENERASI SADAR PEMILU DALAM MENEKAN JUMLAH PELANGGARAN PEMILU - Zahratul'ain Taufik; Putri Raodah; Atika Zahra Nirmala; Nunung Rahmania; Ayu Riska Amalia; Rahmadani Rahmadani (Universitas Mataram, 2023)
Elections are the collective aspiration of the people, as a sacred and honorable event. Violations committed by individuals who, by the rules of their profession, are responsible for upholding the dignity of the democratic process, make it challenging to achieve a dignified selection of leaders. The fact remains that during the 2019 elections, there were more than 16,000 election violations, resulting in 345 criminal verdicts related to elections, handled by the Election Supervisory Agency (Bawaslu) throughout Indonesia. Therefore, the youth are at the forefront in reducing the number of election violations and should be equipped with knowledge and understanding of electoral matters. Hence, we believe it is necessary to optimize the role of youth as a conscious generation for peaceful elections, to better understand the forms of actions that constitute election violations, in order to reduce the number of election violations in Indonesia. This service is carried out through the method of legal outreach, which involves providing explanations about various legal provisions related to prohibited actions during elections and the potential punishments for anyone who violates them. This outreach is conducted through the delivery of materials and discussions. This service has successfully provided a comprehensive understanding of the various types of election violations, starting from administrative violations that can be committed by election participants or organizers, ethical violations that can be committed by election organizers, criminal election violations that can be committed by anyone, to other legal violations that are specifically related to electoral matters, such as the neutrality of civil servants or military/police personnel. All of these violations are handled by the Election Supervisory Agency, resulting in recommendations for rectification to the relevant institutions. The activities conducted have successfully increased the knowledge of the youth regarding the importance of elections and the types of election violations that can disrupt the democratic process.